2012
DOI: 10.1021/pr300147z
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Proteomics by One-Dimensional Gel Electrophoresis Combined with Label-Free Protein Quantification

Abstract: Label-free methods streamline quantitative proteomics of tissues by alleviating the need for metabolic labeling of proteins with stable isotopes. Here we detail and implement solutions to common problems in label-free data processing geared toward tissue proteomics by one-dimensional gel electrophoresis followed by liquid chromatography tandem mass spectrometry (geLC MS/MS). Our quantification pipeline showed high levels of performance in terms of duplicate reproducibility, linear dynamic range, and number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 60 publications
(92 reference statements)
2
37
0
1
Order By: Relevance
“…Gel analyses were performed at the Mass Spectrometry Facility at the Max Planck Institute for Molecular Cell Biology and Genetics (Dresden) on a nano high-performance liquid chromatograph (UltiMate) interfaced on-line to a LTQ Orbitrap Velos hybrid tandem mass spectrometer as described previously (Vasilj et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Gel analyses were performed at the Mass Spectrometry Facility at the Max Planck Institute for Molecular Cell Biology and Genetics (Dresden) on a nano high-performance liquid chromatograph (UltiMate) interfaced on-line to a LTQ Orbitrap Velos hybrid tandem mass spectrometer as described previously (Vasilj et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Eluates were digested with trypsin and subsequently with Lys-C in solution. After addition of protein digests as quantitative standards, the samples were desalted on C-18 stage tips (Nest Group) and analyzed by nanoflow HPLC-MS/MS (2D-NanoLC; Orbitrap Velos MS, Thermo Fisher Scientific; Vasilj et al, 2012). Protein identification was carried out using Mascot V2.2 (Matrixscience) and the determination of peptide ion signals for label-free quantification was performed using Progenesis LCMS V2.6 (Nonlinear Dynamics) and relative quantification was based on the most intense three signals (MI3) (Groessl et al, 2012;Silva et al, 2006).…”
Section: Co-immunopurifications and Quantitative Mass Spectrometrymentioning
confidence: 99%
“…SDS-PAGE of whole-stem and latex protein extracts from the opium poppy chemotype Roxanne contrasted the complexity of each subproteome and revealed the abundance of low molecular mass MLPs in laticifers (Figure 4). Using a gel-based liquid chromatography-tandem mass spectrometry approach (Schirle et al, 2003;Vasilj et al, 2012), 1518 and 511 distinct protein families were identified from the whole-stem and latex samples, respectively. Identification was based on searches of all available plant entries in the National Center for Biotechnology Information nonredundant (NCBInr) database.…”
Section: Shotgun Proteomics Identifies Morphine Biosynthetic Enzymesmentioning
confidence: 99%